The 'host' label: forming and transforming a community identity at the Kakuma refugee camp - Rodgers, C (Oxford University Press, 2020)
In 1986, Robert Chambers argued that refugee-centric responses to displacement tend to neglect the populations that host them. Three decades later, the Comprehensive Refugee Response Framework (CRRF) has made assistance to host communities a matter of high priority for agencies, policymakers and other stakeholders involved in refugee protection. While recognizing the progressive principles of responsibility sharing and inclusivity that underlie this shift, this article calls for greater critical attention to the meaning of the term ‘host community’ and the ways in which it is applied. Taking the Kakuma refugee camps in north-western Kenya as a case study, I describe the rise of a ‘host community’ identity in the context of humanitarian programming, contested attempts to define it as a bureaucratic label and its transformations under a socio-economic-integration agenda. While the case presented here is specific to Kenya, the argument is relevant more broadly as hosts are brought under the purview of refugee-protection policies, especially in countries implementing the CRRF.